Evaluation of the Detection Efficiency of LYSO Scintillator in the Fiber-Optic Radiation Sensor - Chan Hee Park; Arim Lee; Rinah Kim; Joo Hyun Moon (Science and Technology of Nuclear Installations)
The aim of this study was to develop and evaluate fiber-optic sensors for the remote detection of gamma rays in areas that are difficult to access, such as a spent fuel pool. The fiber-optic sensor consists of a light-generating probe, such as scintillators for radiation detection, plastic optical fibers, and light-measuring devices, such as PMT. The (Lu,Y)2SiO5:Ce(LYSO:Ce) scintillator was chosen as the light-generating probe. The (Lu,Y)2SiO5:Ce(LYSO:Ce) scintillator has higher scintillation efficiency than the others and transmits light well through an optical fiber because its refraction index is similar to the refractive index of the optical fiber. The fiber-optic radiation sensor using the (Lu,Y)2SiO5:Ce(LYSO:Ce) scintillator was evaluated in terms of the detection efficiency and reproducibility for examining its applicability as a radiation sensor.